The African Continental Free Trade Area (AfCFTA) : opportunity or pipedream for South Africa’s agricultural exports - Annandale, Desmond Lawrence (Stellenbosch : Stellenbosch University, 2022)
Thesis (MAgricAdmin)--Stellenbosch University, 2022.